2021
DOI: 10.1097/shk.0000000000001885
|View full text |Cite
|
Sign up to set email alerts
|

δPKC-Mediated DRP1 Phosphorylation Impacts Macrophage Mitochondrial Function and Inflammatory Response to Endotoxin

Abstract: Background: Recent studies have demonstrated that alterations in mitochondrial dynamics can impact innate immune function. However, the upstream mechanisms that link mitochondrial dynamics to innate immune phenotypes have not been completely elucidated. This study asks if Protein Kinase C, subunit delta (dPKC)-mediated phosphorylation of dynamin-related protein 1 (Drp1), a key driver of mitochondrial fission, impacts macrophage pro-inflammatory response following bacterial-derived lipopolysaccharide (LPS) stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Targeting mitochondrial fission pharmacologically or genetically can reduce LPS‐triggered proinflammatory responses. [ 32,39 ] In this study, we observed that LPS‐induced mitochondrial fission slightly increased mitophagy and caused significant oxidative stress and inflammation in both macrophages and mouse lung tissue. Interestingly, Kahweol inhibited mitochondrial fission and enhanced mitophagy to remove dysfunctional mitochondria, thus preventing oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 70%
“…Targeting mitochondrial fission pharmacologically or genetically can reduce LPS‐triggered proinflammatory responses. [ 32,39 ] In this study, we observed that LPS‐induced mitochondrial fission slightly increased mitophagy and caused significant oxidative stress and inflammation in both macrophages and mouse lung tissue. Interestingly, Kahweol inhibited mitochondrial fission and enhanced mitophagy to remove dysfunctional mitochondria, thus preventing oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies demonstrated that LPS-induced activation of Drp1 regulates the mitochondrial fission and subsequent inflammatory responses of macrophages and contributes to the promotion of vascular remodeling after injury ( 14 , 15 ). Furthermore, PKCδ-dependent phosphorylation of Drp1 or Stat2-dependent phosphorylation of Drp1-dependent mitochondrial mass increase might be an upstream mechanism that regulates the induction of proinflammatory responses in macrophages ( 16 , 17 ), suggesting that Drp1 plays a crucial role in connecting the changes in mitochondrial dynamics and innate immunity. In contrast, a study showed that KD of Drp1 augmented the activation of NLRP3 inflammasome activation without changing mtROS production or mitochondrial damage ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Drp1 is determined by the phosphorylation status of Ser residues, as phosphorylation at Ser 616 and dephosphorylation at Ser 637 implicate the Drp1 activation. Previous studies showed that Stat2 phosphorylates Drp1 at serine 616 for Drp1-mediated mitochondrial fission ( 44 ) and that protein kinase C (PKC) δ regulates the mitochondrial fission by phosphorylating Drp1 at Ser 616 ( 16 ). Additionally, phosphorylation of Ser 637 in HEK 293T cells is mediated by PKA ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation